Implementasi Latihan Fisik Rehabilitasi Jantung Fase 1 terhadap Kualitas Hidup Pasien Congestive Heart Failure (Chf) - Peri Zuliani; Dita Amita; Shinta Shinta (Universitas Malahayati Lampung, 2023)
ABSTRACT Congestive Heart Failure (CHF) is a clinical syndrome (a set of signs and symptoms) characterized by shortness of breath and fatigue (at rest or during activities). A professional program aimed at helping CHF patients from cardiac arrest, cardiac surgery and percutaneous coronary intervention (PCI) procedures such as stenting and angioplasty is with cardiac rehabilitation. Phase 1 is an effort that is immediately carried out while the patient is still in the treatment period, the main goal of this phase is to reduce or eliminate the adverse effects of deconditioning due to prolonged bed rest, so that the patient is able to carry out his daily activities independently and safely.To determine the effect of phase 1 cardiac rehabilitation exercise on the quality of life of CHF patients.The research design used in this study was a pre-experimental one-group pretest-posttest design. The quality of life score was assessed using the Minnesota Living with Heart Failure Questionnaire (MLHFQ) with 20 statements. The population in this study were all patients who underwent examination with a diagnosis of CHF, the sample in this study were 23 respondents with exclusion and inclusion criteria. The average age of the respondents is 52 years, most of the respondents are 16 people (69.6%), most of the respondents are highly educated, 17 people (73.9%) and most of the respondents are still actively working as many as 16 people ( 69.6%). The results of the paired T-Test statistical test obtained P value = 0.000. Phase 1 cardiac rehabilitation has a significant effect on the quality of life of Congestive Heart Failure patients. Keywords: CHF, Heart, Quality of Life ABSTRAK Congestive Heart Failure (CHF) adalah sindrom klinis (sekumpulan tanda dan gejala) yang ditandai oleh sesak napas dan fatik (saat istirah atau saat beraktivitas). Sebuah program profesional yang bertujuan membantu pasien CHF dari serangan jantung, operasi jantung dan intervensi koroner perkutan (PCI) prosedur seperti stenting dan angioplasty adalah dengan rehabilitasi jantung. Fase 1 merupakan upaya yang segera dilakukan disaat pasien masih dalam masa perawatan, tujuan utama fase ini adalah mengurangi atau menghilangkan efek buruk dari dekondisi akibat tirah baring lama, agar pasien mampu melakukan aktifitas hariannya secara mandiri dan aman. Untuk mengetahui pengaruh latihan fisik rehabilitasi jantung fase 1 terhadap kualitas hidup pasien CHF. Desain penelitian yang digunakan pada penelitian ini adalah pra experimental one-group pretest-posttes design. Penilaian skor kualitas hidup menggunakan Minnesota Living with Heart Failure Questionnaire (MLHFQ) dengan 20 pernyataan. Populasi pada peneltian ini seluruh pasien yang menjalani pemeriksaan dengan diagnosis CHF, sampel pada penelitian ini yaitu sebanyak 23 responden dengan kriteria eksklusi dan inklusi. Rata-rata usia responden 52 tahun, sebagian besar laki-laki berjumlah 16 orang (69,6%), sebagian besar responden berpendidikan tinggi berjumlah 17 orang (73,9%) dan sebagian besar responden masih aktif bekerja sebanyak 16 orang (69,6%). Hasil uji statistik paired T-Test didapatkan nilai P = 0,000. Rehabilitasi jantung fase 1 berpengaruh signifikan terhadap kualitas hidup pasien CHF Kata Kunci: CHF, Jantung, Kualitas Hidup